Use of fuzzy logic to support environmental zoning: A case study in paracatu – mg - Dos Santos, Arthur Pereira [UNESP]; de Paula Santil, Fernando Luiz; de Oliveira, Petronio Silva [UNESP]; Roveda, José Arnaldo Frutuoso [UNESP] (Revista Brasileira de Geografia Fisica, 2021)
The use of geotechnologies to map the levels of environmental fragility in a municipality is an important environmental planning strategy, especially when it is intended to make a conscious use of the area's natural resources through its zoning. Therefore, the objective of this research was to carry out, through the implementation of geotechnologies, a study of environmental fragility in a municipality occupied, intensively, by mining activities and agriculture. As a case study, the municipality of Paracatu-Minas Gerais was adopted. Pedological, lithological, hydrographic, hypsometric, declivity and land use and occupation aspects were raised, in addition to the drainage network, the municipal boundary and mining activity. Finally, using Fuzzy Logic with the use of weights defined by the Analytical Hierarchical Process (AHP) method, the maps of slope, land use and cover, lithology, pedology and drainage network were used to prepare a map of environmental fragility of the municipality. It was concluded that the municipality is susceptible to negative environmental impacts, mainly in its urban network and in the area of open-pit minning, and that these can be better evaluated through the use of geotechnologies aimming at subsidizing urban planning, which is extremely important for the municipality of Paracatu-MG, which is currently undergoing changes in its master plan and intends to expand.
Utilização da lógica fuzzy como suporte ao zoneamento ambiental: Um estudo de caso em paracatu – mg
Keywords: Environmental Planning; Environmental Zoning; Geotechnology